Measurement of ultrafine particles at airports: A review. (1st February 2019) - Stacey, Brian
Abstract: Concern about the health impact of exposure to ultrafine particles has prompted a large number of research studies in the last twenty years. Attention focussed on conventional sources of pollution: vehicle emissions, generation of heat and power, as these are likely to be the most relevant sources of emission to which the general public are exposed. As a result, emissions from road vehicles are well characterised and regulated within Europe. In contrast, until relatively recently, little research into ultrafine particles had been specifically targeted at measurement of direct emissions from aircraft or their potential impact on the communities around airports. As a result, there are a number of gaps in our understanding of these emissions, behaviour in the atmosphere and the potential impact. Aircraft engines, especially the jet turbines used in commercial airliners, are known to emit large quantities of ultrafine particles under a wide range of operating modes, yet detailed information about the physical and chemical properties of these particles is poorly documented. This review aims to outline the background for the development of research studies, summarise the research and assessment of aircraft ultrafine particle emissions, and explore possible areas for future research in this area. Highlights: Brings together key research on UFP from aircraft exhaust measurements. Brings together key research on UFP measurements close to airports. High numbers of particles <20 nm linked to aircraft. Different to normal environments. Provides recommendations for further research. QA/QC procedures need to be better documented to enhance comparability of research.